Alexa, wie hast du's mit der Religion? Theologische Zugänge zu Technik und Künstlicher Intelligenz - Klinge, Hendrik; Kunkel, Nicole; Puzio, Anna (Theologie und Künstliche Intelligenz, 2023)
Technology and artificial intelligence are among the hottest topics in contemporary theology. How can theology contribute to technology and AI? The discourse on technology is charged with religious motifs, and technologies such as robots challenge theology, e.g. B. the image of man, ethics and religious practice, re-emerged. The anthology explores the pressing issues of our time from a theological perspective. To this end, theology enters into dialogue with the technical sciences. The changes in the image of man through robots, religious robots, optimization of the body, medical technologies, auto-regulatory weapon systems and how theology is transformed by technologization are examined. From an interdisciplinary perspective, new research results from the international arena are presented and new paths are explored.